2011
DOI: 10.2903/j.efsa.2011.1989
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 21, Revision 2 (FGE.21Rev2): Thiazoles, thiophene, thiazoline and thienyl derivatives from chemical group 29. Miscellaneous substances from chemical group 30

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 56 flavouring substances in the Flavouring Group Evaluation 21, Revision 2, using the Procedure in Commission Regulation (EC) No 1565/2000. Seven of the substances 15.086, 15.090, 15.099, 15.114, 15.119 and 15.133] were considered to have genotoxic potential. The remaining 49 substances were evaluated through a stepwise approach (the Procedure) that integrates informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In revision 2 of FGE.21 (FGE.21Rev2), the same group of 56 substances was considered (EFSA CEF Panel, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In revision 2 of FGE.21 (FGE.21Rev2), the same group of 56 substances was considered (EFSA CEF Panel, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…(WHO, 2000). Although JECFA concluded that all 12 flavouring substances of CG 29 evaluated were of no safety concern when used at current levels of estimated intake, the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA, 2008(EFSA, , 2011(EFSA, , 2012(EFSA, , 2013a A consortium of companies (the Feed Flavourings Authorisation Consortium (FFAC)) supplying flavours to the feed industry has requested authorisation for the use of the substance 3-acetyl-2,5-dimethylthiophene of CG 29 (Table 2) as an additive to feed and water for drinking (sensory additives, flavouring compounds) for use in all animal species.…”
Section: Terms Of Referencementioning
confidence: 99%